Breaking Stereotypes and Increasing Representation in Marine Biology by Diversifying Children’s Literature - Maria Madrigal; Dieuwertje Kast (Current: The Journal of Marine Education, 2024)
Marian Wright Edelman, Founder and President of the Children’s Defense Fund is credited for saying “You can’t be what you can’t see.” Unfortunately, in both the field of marine biology and in children’s literature, scientists and main characters tend to be predominantly White. In an effort to increase representation and break stereotypes when it comes to people of color, the University of Southern California’s Joint Educational Project (JEP) partnered with a non-profit publisher called Room to Read to create a Science, Technology, Engineering, Arts, and Mathematics (STEAM) Powered Career series. This children’s book series is targeted for ages 6–8 and features three animated characters of color and profiles a gamut of diverse scientists and experts in their fields. Furthermore, to meet the needs of Los Angeles’ large Hispanic communities, the books were translated into Spanish. One of the ten STEAM fields included in the series is Marine Biology which is written by Maria Madrigal and features Dr. Charnelle Wickliff, who are both underrepresented minorities. The book covers marine topics relevant to the local California region such as, kelp forests, tidepools, and even grunion! Room to Read printed over 90,000 free copies that were distributed to low-income families in Los Angeles to address book desert issues.